The role of cleaner production technique in rationalizing costs and enhancing sustainability: Applied research in Al Daura Refinery (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The modern business environment is witnessing tremendous developments in the fields of manufacturing and technology, this improvement requires the development of current production methods to cope with these developments and increasing competition that has exceeded the economic aspects to extend to the environmental aspects, while theexisting traditional systems are inadequate to cope with these developments. The study gained its importance considering that the clean production technique is part of this development in line with the latest developments in the businessenvironment from the risks and conditions surrounding these Economic units through the application of cleaner production technique to eliminate loss, waste of resources and rationalization of costs in the enterprises as well as the elimination of large pollution and emissions from the industry. The current study aims to explain the basic concepts of clean production technique and to demonstrate the vision of the pursuit of clean production technique in rationalizing costs, enhancing sustainability and energyconservation, providing a safe and clean environment for workers and minimizing the waste of the process Productivity. The study is based on key assumption that there is a possibility to achieve economic and environmental goals through the adoption of cleaner production technique to rationalize the cost and preserve natural resources and the environment from pollution. The study concluded with a number of conclusions , the most important of which that the application of clean production technique has a significant impact on rationalization of costs and enhancing sustainability by reducing the pollutants in the oil derivatives industry and preserving the natural resources from waste, In addition to improving the quality of gasoline and avoiding the import of improved gasoline and chemicals from abroad, which are used to improve the quality of the gasoline product The study concluded with a set of recommendations, the most important of which is the need for economic unity to adopt the application of cleaner production technology to rationalize costs and enhance sustainability to reduce pollutants and preserve natural resources to guarantee the right of future generations of these resources.